Enhancing motivation and engagement in economics courses for ‘generation M’ and ‘generation Z’ students - Islam, Shahidul; Alam, Rafat (My University, 2024)
Faculty members continuously try to improve their teaching by adopting new ideas, processes, and procedures. However, we often find a gap between our understanding of what students learn and what students actually learn. The entire premise of today's learning is based on a teacher-student hierarchical model. The models of enhancing student motivation suggest breaking out of this hierarchical knowledge transfer. Despite the breadth and quality of the existing Scholarship of Teaching and Learning (SoTL) work, surprisingly little is known about students characterize their learning experiences. The few studies that have prominently carried the "voices" of university students date back to the 1980s and, therefore, do not incorporate the insights of an entirely new generation -- the Millennials or Generation M. All the other priorities of the general life and academic life of generation M compete with their motivation to learn. This paper fills a gap in research by analyzing the opinions of Generation M students, attempting to understand what factors are related to the motivation, engagement, and participation of Generation M undergraduate students in economic course, and examining how students' motivation may contribute to their success and failure in economics courses, as well as what can be done to increase their motivation.
Keywords: Millennials; Generation M; teacher-student hierarchical model; undergraduate economics